Mammal decline, linked to invasive Burmese python, shifts host use of vector mosquito towards reservoir hosts of a zoonotic disease. (31st October 2017) - Hoyer, Isaiah J.; Blosser, Erik M.; Acevedo, Carolina; Thompson, Anna Carels; Reeves, Lawrence E.; Burkett-Cadena, Nathan D.
Abstract : Invasive apex predators have profound impacts on natural communities, yet the consequences of these impacts on the transmission of zoonotic pathogens are unexplored. Collapse of large- and medium-sized mammal populations in the Florida Everglades has been linked to the invasive Burmese python, Python bivittatus Kuhl. We used historic and current data to investigate potential impacts of these community effects on contact between the reservoir hosts (certain rodents) and vectors of Everglades virus, a zoonotic mosquito-borne pathogen that circulates in southern Florida. The percentage of blood meals taken from the primary reservoir host, the hispid cotton rat, Sigmodon hispidus Say and Ord, increased dramatically (422.2%) from 1979 (14.7%) to 2016 (76.8%), while blood meals from deer, raccoons and opossums decreased by 98.2%, reflecting precipitous declines in relative abundance of these larger mammals, attributed to python predation. Overall species diversity of hosts detected in Culex cedecei blood meals from the Everglades declined by 40.2% over the same period ( H (1979) = 1.68, H (2016) = 1.01). Predictions based upon the dilution effect theory suggest that increased relative feedings upon reservoir hosts translate into increased abundance of infectious vectors, and a corresponding upsurge of Everglades virus occurrence and risk of human exposure, although this was not tested in the current study. This work constitutes the first indication that an invasive predator can increase contact between vectors and reservoirs of a human pathogen and highlights unrecognized indirect impacts of invasive predators.